2021
DOI: 10.1186/s12885-021-08738-z
|View full text |Cite|
|
Sign up to set email alerts
|

Prospective observational study on Pazopanib in patients treated for advanced or metastatic renal cell carcinoma in countries in Asia Pacific, North Africa, and Middle East regions: PARACHUTE study

Abstract: Background Clinical effectiveness and safety data of pazopanib in patients with advanced or mRCC in real-world setting from Asia Pacific, North Africa, and Middle East countries are lacking. Methods PARACHUTE is a phase IV, prospective, non-interventional, observational study. Primary endpoint was the proportion of patients remaining progression free at 12 months. Secondary endpoints were ORR, PFS, safety and tolerability, and relative dose intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
1
6
1
Order By: Relevance
“…Due to financial constraints and a limited access program, it was a major challenge to offer TKI plus ICI or double ICI in combination to our patients. Despite this limitation, the clinical benefit rate (81%) in our study was quite impressive and even higher than published data from Asia Pacific countries [ 10 , 16 - 18 ].…”
Section: Discussioncontrasting
confidence: 74%
“…Due to financial constraints and a limited access program, it was a major challenge to offer TKI plus ICI or double ICI in combination to our patients. Despite this limitation, the clinical benefit rate (81%) in our study was quite impressive and even higher than published data from Asia Pacific countries [ 10 , 16 - 18 ].…”
Section: Discussioncontrasting
confidence: 74%
“…Hypothyroidism and proteinuria were also among the most common treatment‐related AEs observed in a phase 1 study of lenvatinib plus pembrolizumab in Japanese patients with advanced solid tumors, although no data on outcomes in patients with endometrial cancer were available 10 . Increased incidences of these AEs have been previously reported in Asian patients receiving VEGF or VEGF receptor inhibitors 11–15 . A number of hypotheses have been proposed to explain the higher incidence of such events among Asian patients receiving VEGF receptor inhibitors, including lower body weight/body surface area and/or genetic differences; evidence supporting these hypotheses has been equivocal 12,16 .…”
Section: Discussionmentioning
confidence: 99%
“…10 Increased incidences of these AEs have been previously reported in Asian patients receiving VEGF or VEGF receptor inhibitors. [11][12][13][14][15] A number of hypotheses have been proposed to explain the higher incidence of such events among Asian patients receiving VEGF receptor inhibitors, including lower body weight/body surface area and/ or genetic differences; evidence supporting these hypotheses has been equivocal. 12,16 Although the incidence of these events was in-…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in the author names of Mustafa Erman, Bivas Biswas, Pongwut Danchaivijitr, Lingwu Chen and Chandrasekhar Chikatapu. The given names and family names were erroneously transposed.…”
mentioning
confidence: 99%